2013
DOI: 10.1016/j.jneuroim.2013.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin-sensitive vagal afferent neurons contribute to the detection of pathogenic bacterial colonization in the gut

Abstract: Vagal activation can reduce inflammation and disease activity in various animal models of intestinal inflammation via the cholinergic anti-inflammatory pathway. In the current model of this pathway, activation of descending vagal efferents is dependent on a signal initiated by stimulation of vagal afferents. However, little is known about how vagal afferents are activated, especially in the context of subclinical or clinical pathogenic bacterial infection. To address this question, we first determined if selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 57 publications
2
41
0
Order By: Relevance
“…Indeed, indole can modify epithelial cells and tight junction proteins (Bansal et al, 2010). Consistent with the importance of the vagus in informing the CNS about changes in the gut microbiome (Bercik et al, 2011;Bravo et al, 2011;Riley et al, 2013), electrophysiological studies demonstrated that application of indole to the mucosa, but not directly onto exposed intrinsic or extrinsic neurons, resulted in GLP-1R-dependent activation of vagal afferents. In terms of gut-brain axis wiring, most innervation of small intestinal epithelial cells is by submucosal neurons (Keast et al, 1984;Ekblad et al, 1987) and intrinsic primary afferent neurons may act as the starting point in gut-brain signaling (Perez-Burgos et al, 2014).…”
Section: Discussionmentioning
confidence: 85%
“…Indeed, indole can modify epithelial cells and tight junction proteins (Bansal et al, 2010). Consistent with the importance of the vagus in informing the CNS about changes in the gut microbiome (Bercik et al, 2011;Bravo et al, 2011;Riley et al, 2013), electrophysiological studies demonstrated that application of indole to the mucosa, but not directly onto exposed intrinsic or extrinsic neurons, resulted in GLP-1R-dependent activation of vagal afferents. In terms of gut-brain axis wiring, most innervation of small intestinal epithelial cells is by submucosal neurons (Keast et al, 1984;Ekblad et al, 1987) and intrinsic primary afferent neurons may act as the starting point in gut-brain signaling (Perez-Burgos et al, 2014).…”
Section: Discussionmentioning
confidence: 85%
“…In addition, it has been shown that both vagal and spinal afferent neurons do not only respond to these microbial and immune messengers but can also, under their influence, undergo sensitization to other stimulants. For instance, both LPS and tumor necrosis factor-α (TNF- α) are capable of directly activating vagal afferent neurons in culture ( 71 ). In addition, LPS can stimulate sensory neurons via activation of the transient receptor potential ankyrin-1 (TRPA1) ion channel ( 72 ) and sensitize afferent fibers in mesenteric nerves to serotonin, bradykinin, and gut distension, an effect in which mast cells and cyclooxygenase-2 play a role ( 73 ).…”
Section: Immune Stress Signaling From the Gut To The Brainmentioning
confidence: 99%
“…45 Evidence suggests that this parasympathetic neuroimmune reflex is dependent on vagal afferent neurons for the local release of intestinal inflammatory mediators in response to pathogenic gut bacteria. 46 Therefore, elevated vagal tone and parasympathetic influence, as seen in the resting state of athletes, may foster a preferential antiinflammatory milieu at the intestinalluminal interface, with an attendant conditioning influence on microbial composition.…”
Section: Introductionmentioning
confidence: 99%